The Guidelines for Promoting Morality and Ethics in the Parivāsakamma Meritorious Activity, Phen District, Udon Thani Province - Dhammadinno , Phra Nattan; Phramaha Daosayam Vajirapañño; Phra Soponphanabundit (Dhammathas Academic Journal, 2022)
The objectives of this research were: 1) to study the promotion of morality and ethics in the Parivāsakamma meritorious activity during the Buddha’s time; 2) to study the promotion of morality and ethics in the Parivāsakamma meritorious activity in Phen District, Udon Thani Province, and 3) to study the guidelines for promoting morality and ethics in the Parivāsakamma meritorious activity in Phen District. This study was carried out by means of qualitative research by collecting the documents and in-depth interviews. The obtained data were interpreted by a descriptive writing. The research results were as follows: 1. The Parivāsakamma meritorious activity of monks has existed since the Buddha’s time. This activity appears in the Dhamma Vinaya and the Tipitaka in four types: 1) Appaṭicachannaparivāsa (Parivāsa for laypeople); 2) Paṭicachannaparivāsa; 3) Samodhānaparivāsa; 4) Sudadhantaparivāsa. 2. The Parivāsakamma meritorious activity of Wat Roi Phra Phutthabat Naruenat, Tao Hai Subdistrict Community, Phen District, Udon Thani Province is organized as the Cuḷasudadhantaparivāsa in nine nights and ten days due to its convenience of practice. 3. The Parivāsakamma of monks affects the Buddhist community of Tao Hai Subdistrict, Phen district, Udon Thani province. In addition to the practice of monks and those who are interested, it encouraged people in the community to perform giving in order to build friendship and relationships among the people in the community, to keep the precepts and to keep the body and speech, do not cause trouble for the people in the community. People also cultivated compassion, and this made them become good people or complete human beings with good morals and ethics because of the correct learning. This created a strong community, and the community members have knowledge and understanding in the same direction. They were able to practice correctly according to the doctrine, resulting in many aspects such as oneself, family, society, Buddhism, culture, customs, politics, and governance.